Analisis dan Perancangan Sistem Raport Digital Metode Waterfall - Mochammad Bagoes Satria; Hendri Ardiansyah (Journal on Education, 2023)
In today's modern era, coupled with the recent pandemic, this has forced the world of education to adapt to technological developments that are developing very rapidly. Various sectors of education, both formal and informal, continue to improve in various ways, starting from learning methods, learning media to learning outcomes, which we know as report cards. Digital report cards are not something that is relatively new in Indonesian education, and Yapan Indonesia Vocational School is no exception. So far, the reporting of learning outcomes is conveyed through printed paper and put in a folder which is then handed over at a certain time to the parents of students. When the pandemic hit, this became a problem because government regulations that limited citizens' mobility seemed to impede ongoing communication between the school and parents. Not to mention the several problems that occurred when the report cards provided in the form of sheets of paper were wet, torn or lost which caused the school to have to reprint it many times. The waterfall method is used because the waterfall method is a method that works in a structured and systematic way, starting from the stage of analyzing the required system requirements, then continuing with analysis, moving to the design stage, then coding, and ending with testing or trials, and carrying out maintenance. The results obtained are a digital report card system that is practical to use and can minimize the risk of damage and loss of data